2019
DOI: 10.1016/j.jtcvs.2018.07.107
|View full text |Cite
|
Sign up to set email alerts
|

Elevated gradient after mitral valve repair: The effect of surgical technique and relevance of postoperative atrial fibrillation

Abstract: Objectives: We sought to investigate the effect of surgical technique in mitral valve repair on postoperative transmitral gradient (PTMG) and the relationship between PTMG and postoperative atrial fibrillation (AF).Methods: In this retrospective study, 390 patients who underwent mitral valve repair for degenerative mitral regurgitation without AF were included. PTMG was measured using transthoracic echocardiography before patient discharge. At follow-up, occurrences of AF within 6 months of surgery (early AF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
5
22
0
2
Order By: Relevance
“…2 Previous work suggests that a gradient exceeding 3 mm Hg can result in impaired exercise tolerance. 2 Adding to this observation, Ma and colleagues 1 found that a gradient exceeding 4.5 mm Hg substantially increases the risk of late AF. Taken together, these findings suggest that the surgeon should repair the valve using techniques that correct MR and prevent MS. Ma and colleagues 1 help with this task by identifying repair techniques associated with higher gradients.…”
Section: Marc Gillinov MD Per Wierup Md Phd and Stephanie Mick Mdmentioning
confidence: 94%
See 1 more Smart Citation
“…2 Previous work suggests that a gradient exceeding 3 mm Hg can result in impaired exercise tolerance. 2 Adding to this observation, Ma and colleagues 1 found that a gradient exceeding 4.5 mm Hg substantially increases the risk of late AF. Taken together, these findings suggest that the surgeon should repair the valve using techniques that correct MR and prevent MS. Ma and colleagues 1 help with this task by identifying repair techniques associated with higher gradients.…”
Section: Marc Gillinov MD Per Wierup Md Phd and Stephanie Mick Mdmentioning
confidence: 94%
“…The implications of Ma and colleagues' work 1 extend beyond surgical repair of degenerative disease. As with aortic valve replacement, when performing mitral replacement, it may be prudent to choose the largest and most hemodynamically efficient prosthesis to avoid elevated gradients.…”
Section: Marc Gillinov MD Per Wierup Md Phd and Stephanie Mick Mdmentioning
confidence: 99%
“…I read with interest the insightful commentary of Tom si c and colleagues 1 exploring the influence of annuloplasty prosthesis type on postoperative valvular gradients after mitral repair for degenerative disease, as reported by Ma and associates. 2 As duly outlined by Tom si c and colleagues, 1 providing detailed characteristics of the type of prostheses, both complete and partial, used in the study would provide greater clarity to the presented data. Ignoring the potential difference in annular reduction between partial and complete annular prostheses, however, may be a comparable fallacy.…”
Section: The Devil Is Everywhere Including the Details Of The Ring Rmentioning
confidence: 99%
“…We thank Dr Tom si c and colleagues for their response to our study investigating the risks of elevated transmitral gradient (TMG) and its association with late atrial fibrillation (AF). 1,2 One of their concerns was the device-specific difference in prosthetic orifice area, because rings with the same labeled diameter did not have the same area. We agree with this point, and in our last study we used prosthetic orifice area as the key variable instead of ring size in subgroup analysis of patients undergoing full ring annuloplasty.…”
mentioning
confidence: 99%
“…За наявності супутніх надшлуночкових порушень ритму, діагностованих перед процедурою, ризик післяопераційної ФП збільшується до 60 %. ФП у пацієнтів кардіохірургічного профілю призводить до значних порушень гемодинамічної функції серця в періопераційний період, що збільшує ймовірність виникнення післяопераційних ускладнень, які можуть призводити до смерті та збільшення термінів госпіталізації [20]. У дослідженні CODACS (Consciousness Disorders After Cardiac Surgery) надшлуночкові порушення ритму були діагностовані у 78,3 % хворих кардіохірургічного профілю із ФП, виявленою до втручання [26].…”
unclassified